Perception and management of risks in the shrimp sector, empirical results of producers in the province of El Oro, Ecuador. - Ordoñez C., James W. (Zamorano: Escuela Agrícola Panamericana, 2021., 2021)
This study was conducted to explore shrimp farmers’ perceptions of risk and risk management. The data used originated from a field survey in the southern coasts of Ecuador, El Oro. There are many studies dedicated to the study of aquaculture´s risks, but there is a need to know about the shrimp farmers' perception of risks and the strategies they used to mitigate them. Therefore, this document explores: (a) farmers 'perceptions of risks and their management responses and (b) farmers' socio-economic characteristics in terms of their risk perceptions and risk management strategies. Farm-level data were collected through a sample recognition survey of 79 shrimp farms. The exploratory factor analysis showed that the risks in shrimp farming are derived from five factors: Policy and finance; Market and costs; Weather and environment; Lack of technical knowledge; and Production management. The results also revealed that the risk perception of shrimp farmers could significantly influence their risk management behavior. In addition, seven factors were identified for risk management strategies, including government support and risk sharing; education and technology improvement; implementation of good production practices; corrective management; disease prevention; contract external assistance; and marketing.